Musical Preferences of Pupils - Komerički, Ida (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter examines the influence of various personal factors, such as age, gender, musical training, and social influence, on musical preferences. The importance of age in shaping musical tastes is emphasized, with younger individuals being more open to diverse genres and types of music. This openness tends to decline with age, leading older individuals to be less receptive to certain musical styles. Research also indicates that girls often exhibit a broader range of musical preferences. Musical training plays a significant role in shaping tastes, as higher levels of education are associated with an increased inclination toward "serious" musical genres. Social influence, particularly exposure to music through the media, further shapes musical preferences. The aim of this chapter is to explore how personal factors and social influences contribute to the formation of musical tastes, particularly in younger individuals.